Ownership structure impact on Jordanian banks’ financial performance - Jarbou, Loay Saleh; Abu-Serdaneh, Jamal; Mahd, Osama Abdel Latif (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study seeks to examine the effect of ownership structures on the Jordanian commercial banks’ performance for the period 2005 -2014. It also aims to investigate the impact of the bank’s characteristics on the performance. This study uses Return on Investment and Return on Equity to assess the financial performance of the banks. The ownership structure was measured using ownership concentrations, institutional ownership, foreign ownership, and government ownership. Bank characteristics were also covered using size, age and debt to equity ratio. The study has shown that the banks’ profitability significantly decreases with a high ownership concentration, larger banks’ size, and higher debt to equity ratio. Meanwhile, the foreign ownership and government ownership have a significant positive impact on the banks’ performance. Moreover, the results found no impact for the institutional ownership and the age on the performance of Jordanian banks.